The association between declining lung function and stroke risk: insights from an observational study and Mendelian randomization - Wang, Jiadong; Lin, Junjie; Zheng, Yujie; Hua, Minxia; Wang, Kunyi; Lu, Kexin; Zhang, Yu; Zheng, Weijun; Chen, Rucheng; Lin, Fuquan (Frontiers in Neurology, 2024)
Background Stroke, prevalent globally, particularly impacts low- and middle-income countries. Decreased lung function is one of the risk factors for stroke, and there is a lack of sufficient research on the association between the two, especially based on evidence from representative large samples. We aimed to explore the association between lung function and stroke incidence. Methods We collected data from 13,371 participants from the 2007–2012 U.S. national cross-sectional study and 11,192 participants from the Chinese national cohort study during the 2011–2018 follow-up period. Multivariate logistic regression and Cox proportional hazards regression were used to assess cross-sectional and longitudinal associations of peak expiratory flow with stroke risks. Additionally, we used publicly available GWAS data from a European population to conduct Mendelian randomization analysis, further exploring the potential causal relationship. Results The results of the cross-sectional study suggest that a decline in peak expiratory flow may be associated with an increased risk of stroke. The cohort study revealed that, compared to the first tertile group, the risk of stroke incidence in the second and third tertile groups of PEF decreased by 19% (hazard ratio (HR) = 0.810, 95%CI = 0.684–0.960) and 21.4% (HR = 0.786, 95%CI = 0.647–0.956), respectively. Mendelian randomization analysis clarified that higher PEF levels are significantly associated with a reduced risk of stroke (OR = 0.852, 95%CI = 0.727–0.997). Conclusion Decreased lung function is a risk factor for stroke. As a simple and accurate indicator of lung function, PEF can be used to monitor lung function in community populations and patients for primary stroke prevention.